Busting MisconSEXions: evaluation of a social media knowledge translation initiative addressing myths about sex - O’Kane, Kiarah M. K.; Goldberg, Simone Y.; Bouchard, Katrina N.; Dawson, Samantha J. (Frontiers in Psychology, 2024)
There is a critical gap in sex education such that many people lack access to evidence-based and accessible information about sexuality, putting them at risk for endorsing myths about sex and in turn having poorer sexual well-being. To address this gap, we developed a novel social media knowledge translation initiative—MisconSEXions—to debunk common myths about sexuality. The goal of this study was twofold. First, to examine whether exposure to MisconSEXions is effective for reducing sexuality myth endorsement. Second, to evaluate the implementation of MisconSEXions with respect to its acceptability (participants’ satisfaction with the content), appropriateness (the perceived fit of the content with participants), adoption (participants’' intention to engage with the initiative), and penetration (participants’ perception of the content’s impact on their lives) of MisconSEXions among study participants. We also examined possible group differences in our observed effects by assigned sex, gender modality, and sexual orientation. A large and diverse sample (N = 2,356) of adults completed an online survey and reported on their demographics, sexuality myth endorsement before and after exposure to MisconSEXions content, and implementation of the acceptability, appropriateness, adoption, and penetration of the MisconSEXions content. We found that participants’ sexuality myth endorsement was significantly lower following exposure to MisconSEXions content, and this effect held across assigned sex, gender modality, and sexual orientation groups. Regardless of participants’ assigned sex, gender modality, or sexual orientation, MisconSEXions content was reported to be both acceptable and appropriate to people’s lives. Participants reported relatively low levels of adoption, such that they reported reluctance to engage with the content on social media. Additionally, participants reported mixed feelings regarding the impact of the content on their lives (i.e., penetration). Overall, the findings have implications for how sexuality social media knowledge translation initiatives can fill important gaps in providing inclusive and accessible sex education.